The Impact of Food Authenticity, Price Fairness, and Cultural Similarity on Satisfaction and Purchase Intention at Indonesian Restaurants in Taiwan - Hatma, Ramli; Rachman, Abdul Nasir; Musa, Andi Ernie Zaenab; Hardiyono, Hardiyono; Latiep, Ifah Finatry (Politeknik Negeri Bandung, 2025)
This study looks at how customer happiness, brand awareness, and purchase intention are affected by cuisine authenticity and fair prices at Indonesian restaurants in Taiwan. Partial Least Squares (PLS) and Structural Equation Modelling (SEM) were used to analyze a survey of 400 foreign clients. The findings support the notion that fair prices and real cuisine both increase consumer happiness, which raises brand recognition and buy intent. The association between cuisine authenticity and consumer pleasure is moderated by cultural similarity, with customers who share a common culture reporting higher levels of satisfaction. At a 10% significant level, it also moderates the association between price fairness and satisfaction, indicating that cultural alignment may boost price variation tolerance. These results emphasize how crucial fair pricing and authenticity are to building client loyalty and drawing in a larger audience. However, the study only looks at foreign consumers; for a more thorough knowledge of consumer behaviour, future studies need look at local Taiwanese consumers as well as other aspects like ambiance and service quality.